Transformational leadership on organizational infrastructure resources: Evidence from Malaysian construction organizations - Khairul Firdaus, Anuar; Nurhaizan, Mohd Zainudin; Muhammad Ashraf, Fauzi (Global Academy of Training and Research (GATR) Enterprise, 2025)
Objective - This study investigates the impact of Transformational Leadership (TL) on organizational infrastructure resources; Knowledge Sharing (KS), Human Resource Management (HRM) and Top Management Commitment (TMC) in Malaysian construction organizations. Grounded in the Contingency Theory, this research posits that TL is strategic in nature by assisting in aligning internal capabilities to performance goals within a project-driven environment. Methodology - Adopting a quantitative methodological approach, data from 155 construction professionals were collected and analyzed by utilizing Partial Least Squares-Structural Equation Model (PLS-SEM) analysis. Findings - The results of empirical study reveal that TL has a significant positive influence on all three KS dimension (KS among projects, KS within projects and KS within organizations), HRM and TMC. These results highlight the importance of TL for knowledge-oriented collaboration, intensified HR practices and strengthening executive alignment. Novelty - The research adds to the leadership and construction management literature by presenting the significant empirical proof of organizing the TL into the organization’s infrastructure. Practical implications argue for the institutionalization of TL-based leadership development and its inclusion in HRM and strategic governance practices to enhance organizational performance in construction firms.